106 Audit of effectiveness of in-patient clinical management escalation plan. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Vincent, Cathrine; Day, Peter; Chauhan, Alpna
Abstract : Background: In 2017, a formal escalation planning process for the management of patients at a hospice inpatient unit was initiated in response to the inappropriate transfer of a patient to the acute setting out-of-hours. This initiative involves formation of an escalation plan (EP) in advance consisting of one of three categories; supportive hospice care, hospice escalation or hospital escalation. Aims and objectives: This study aims to answer the question 'Does advanced escalation planning and documentation improve patient care?' Methods: Data was collected retrospectively of 50 cases from the in-patient unit 1 year after the EP plan process was commenced. A staff questionnaire was also included. The notes were reviewed for details of any treatment escalations that occurred or were considered and this was compared to their escalation plan at the time. Results: The process is being used effectively with 94% of patient's having an EP documented. There were 45 escalation events, mostly for symptom control, and nearly half the patients had at least 1 event during their admission which reflects the current level of intervention in palliative care. In 36% the acute hospital was involved for symptom control and diagnostic investigations. 4% were appropriately transferred from the hospice to the hospital for in-patient care. Escalation events matched the EP in 88% and where they didn't this involved patient choice or a rapid change in the patient's condition. The staff who engaged with the staff questionnaire reported finding the EP helpful. Conclusion: This audit shows overall positive results of engagement and clinical outcomes of this new initiative. It shows plans are formed in advance, they are documented, and clinical judgment is being used in individual situations to ensure appropriate clinical treatments are offered and outcomes are of benefit to the patient.